Hip Fracture in the Elderly Patients: A Sentinel Event. (April 2018) - Koso, Riikka E.; Sheets, Charles; Richardson, William J.; Galanos, Anthony N.
Importance: Hip fracture in the elderly patients is associated with increased morbidity and mortality. There is great need for advance care planning should a patient fail to rehabilitate or experience an adverse event during or after recovery. This study was performed to evaluate for palliative care consultation and changes in code status and/or advance directives in elderly patients with hip fracture. Methods: We performed a retrospective review of 186 consecutive patients aged 65 years and older with a hip fracture due to a low-energy fall who underwent surgery at a large academic institution between August 1, 2013, and September 1, 2014. Risk factors assessed were patient demographics, home status, mobility, code status, comorbidities, medications, and hospitalizations prior to injury. Outcomes of interest included palliative care consultation, complications, mortality, and most recent code status, mobility, and home. Results: About 186 patients with hip fractures were included. Three patients died, and 12 (6.5%) sustained major complications during admission. Nearly one-third (51 patients) died upon final follow-up approximately 1.5 years after surgery. Of the patients who died, palliative care consulted on 6 (11.8%) during initial admission. Eleven (21.6%) were full code at death. Three patients underwent cardiopulmonary resuscitation (CPR) and 1 underwent massive transfusion and extracorporeal membrane oxygenation prior to changing their code status to do not attempt resuscitation. Conclusion: Hip fracture in elderly patients is an important opportunity to reassess the patient's personal health-care priorities. Advance directives, goals of care, and code status documentation should be updated in all elderly patients with hip fracture, should the patient's health decompensate.